2019
DOI: 10.1002/bse.2396
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable entrepreneurship, innovation, and business models: Integrative framework and propositions for future research

Abstract: This article introduces the business models for sustainability innovation (BMfSI) framework to study how business models mediate between sustainability innovations and business cases for sustainability. The BMfSI framework integrates two major perspectives (implicitly) found in the sustainable business model literature. The first is the agency perspective. It takes into consideration that some form of agency is needed, that is, "someone" who takes decisions and acts. Sustainable entrepreneurs are discussed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
197
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(207 citation statements)
references
References 94 publications
(262 reference statements)
5
197
0
5
Order By: Relevance
“…They are able to overcome existing challenges by leveraging the growing consumer awareness, value chain partnerships, IT, social networks and sustainability-focused policies, to launch innovative products or services which offer time or cost savings, quality service, and a range of social and environmental benefits. In this process they help educate and influence other important actors such as NGOs, large companies, and policy makers, confirming previous research by Geels (2010) and Ludeke-Freund (2020) . Sustainability entrepreneurs, however, are unable to achieve a market effect and a shift to SLs on their own, which requires political support and new regulations.…”
Section: Conclusion and Future Prospectssupporting
confidence: 82%
See 3 more Smart Citations
“…They are able to overcome existing challenges by leveraging the growing consumer awareness, value chain partnerships, IT, social networks and sustainability-focused policies, to launch innovative products or services which offer time or cost savings, quality service, and a range of social and environmental benefits. In this process they help educate and influence other important actors such as NGOs, large companies, and policy makers, confirming previous research by Geels (2010) and Ludeke-Freund (2020) . Sustainability entrepreneurs, however, are unable to achieve a market effect and a shift to SLs on their own, which requires political support and new regulations.…”
Section: Conclusion and Future Prospectssupporting
confidence: 82%
“…al. 2017 ; Horisch, 2015; Ludeke-Freund, 2020 ). For instance, the proliferation of Fixit Clinics in the U.S. has attracted the support of politically-active public advocacy groups which are working with citizens and progressive policy makers to adopt new “Right to Repair” mandates at state levels (U.S. PIRG, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some literature review studies indicated that social system dimensions [65] and sustainability integration [66] can potentially become new themes of SBM. Luedeke-Freund [67] explored how business models achieve sustainability by balancing sustainable innovation with business cases and summarized two research perspectives, namely the agency and system perspectives.…”
Section: Sustainable Business Modelmentioning
confidence: 99%